Software Testing - Gupta, Harish (New Delhi, 2010)
Testing is not considered to be part of the Project Management approach. More often, it is defined within the methodology being used or in a specific testing methodology. However, most Project Managers have to deal with technology development and all should wish to test their solutions before moving into live operations.
Keywords: Computer Software-Testing